(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The article examines youth slang as an important element of modern speech culture. The influence of Internet communication and popular youth subcultures on the formation of new lexical units is analyzed. Particular attention is paid to slang associated with anime culture and Korean pop music (K-pop). The history of the emergence of slang expressions within these subcultures is considered, examples of words are provided, and the features of their functioning in youth speech are analyzed. The role of Internet communication and fan communities in the spread of slang is also examined. The paper presents a comparative analysis of different types of youth vocabulary and discusses the process by which subcultural slang spreads beyond its original environment of use.